Narrow-width titanium-aluminum solid-liquid composite material, method for manufacturing the same, and applications
Patent Information
- Application Number
- JP2025541138
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-28
- Filing Date
- 2025-04-29
- Publication Date
- 2026-10-14
Smart Images

Figure 2026533924000001_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of titanium composite material processing, and in particular to a narrow-width titanium-aluminum solid-liquid composite material.
Background Art
[0002] The metal layered composite plate is manufactured from two or more types of metal plates with different properties by a special processing method. The special processing methods for the metal layered composite plate mainly include cast-rolling compounding, friction welding and explosive welding. The semi-finished metal layered composite plate obtained by cast-rolling compounding, friction welding or explosive welding needs to be subjected to annealing treatment to remove the internal stress caused by the special processing between the metal plates, and finally finished by finish rolling, forming and polishing, so that the finished metal layered composite plate can be obtained. The produced metal layered composite plate combines the respective superior physical and chemical properties of two or more metal components. Compared with a single plate material, the metal layered composite plate obtains comprehensive properties that no single metal has, which greatly expands the application range of the metal layered composite plate.
[0003] Titanium-aluminum alloy has excellent advantages such as high strength, low density, good toughness and good corrosion resistance, and is widely used in the fields of 3C consumer electronic products, aerospace, petrochemical industry, transportation and new energy vehicles.
[0004] In actual industrial production, titanium / aluminum composite sheets are already produced. For example, in the method for manufacturing layered titanium-aluminum steel composite strip coils disclosed in disclosure no. CN112090961A, in step 1, pure titanium strip coil raw material, aluminum strip coil raw material, and stainless steel strip coil raw material are placed in corresponding uncoilers, with the aluminum strip coil raw material positioned in the middle and the pure titanium strip coil raw material and stainless steel strip coil raw material positioned above and below the aluminum strip coil raw material, respectively. In step 2, the pure titanium strip coil raw material, aluminum strip coil raw material, and stainless steel strip coil raw material are unwound simultaneously, and the three strip coil raw materials are simultaneously placed in assembly line processing equipment at the same transport rate to perform composite rolling to obtain an initial composite strip coil product. The initial composite strip coil product is then annealed to obtain a finished composite strip coil, i.e., layered titanium-aluminum steel composite strip coil material, which has good corrosion resistance, wear resistance, non-toxicity, antibacterial properties, magnetic conductivity, and thermal conductivity, and also improves the interlayer bonding strength of the composite strip coil material.
[0005] Conventional titanium / aluminum composite sheets, while possessing good mechanical strength, still exhibit interlaminar bonding performance (peel strength) less than 50 N / mm, representing a processing method that sacrifices interlaminar bonding strength to improve overall mechanical strength. To obtain titanium-aluminum composite metal strips with high bonding strength and high mechanical performance simultaneously, the inventors provide a narrow titanium-aluminum solid-liquid composite material, a method for manufacturing the same, and its applications. [Overview of the Initiative] [Problems that the invention aims to solve]
[0006] To address the problem that conventional titanium / aluminum composite sheets cannot possess both mechanical strength and bonding strength, the present invention provides a narrow titanium-aluminum solid-liquid composite material, a method for producing the same, and its applications. [Means for solving the problem]
[0007] The narrow titanium-aluminum solid-liquid composite material according to the present invention is realized by the following solution.
[0008] The narrow titanium-aluminum solid-liquid composite material comprises a titanium strip and an aluminum strip formed by casting and rolling liquid aluminum, wherein the titanium strip is made of pure titanium or a titanium alloy, and the aluminum strip is made of one of the following: 1-series pure aluminum, 3-series aluminum alloy, 5-series aluminum alloy, and 6-series aluminum alloy, and the peel strength between the titanium strip and the aluminum strip is ≥ 60 N / mm². 2 The narrow titanium-aluminum solid-liquid composite material has a tensile strength of ≥300 MPa, a yield strength of ≥200 MPa, a composite surface shear strength of ≥180 MPa, and an elongation of ≥20%.
[0009] The titanium-aluminum solid-liquid composite material manufactured according to the present invention possesses excellent mechanical strength and bonding strength. When used in the 3C consumer electronics field, it contributes to improving the appearance and texture of smartphones, while also significantly reducing the weight of the device, thus meeting the demand for lightweight smartphone designs. The narrow titanium-aluminum solid-liquid composite material according to the present invention can be manufactured by processing the material into irregularly shaped titanium-aluminum solid-liquid composite materials, including but not limited to molded materials, strip materials, and sheet materials.
[0010] The method for producing a narrow titanium-aluminum solid-liquid composite material according to the present invention is realized by the following technical proposal.
[0011] In the method for manufacturing narrow-width titanium-aluminum solid-liquid composite materials, first, titanium strips and liquid aluminum are cast and rolled together to obtain a rough titanium-aluminum composite strip material. Then, the rough titanium-aluminum composite strip material is subjected to a hot finishing rolling process at 400-600°C with a large amount of deformation to obtain a first-grade titanium-aluminum composite strip material. After cooling, a cold finishing rolling process with a small amount of deformation is performed to obtain a second-grade titanium-aluminum composite strip material. Finally, the second-grade titanium-aluminum composite strip material is straightened and polished to obtain the finished narrow-width titanium-aluminum solid-liquid composite material.
[0012] Preferably, the ratio of the thickness of the titanium strip to the thickness of the aluminum strip in the titanium-aluminum composite strip material is 1:(2~3).
[0013] More preferably, the ratio of the thickness of the titanium strip to the thickness of the aluminum strip in the titanium-aluminum composite strip material is 1:2. The amount of deformation of the titanium-aluminum composite strip material during the hot finishing rolling process with large deformation is 50-70%.
[0014] In a cold finishing rolling process with small deformation, the number of cold finishing rolls is one or two. The total deformation of the Grade 1 titanium-aluminum composite strip material during the cold finishing rolling process is 2-10%, and the deformation of a single pass is ≤5%.
[0015] Preferably, in the specific manufacturing method of the titanium-aluminum composite strip material, an aluminum alloy is melted to obtain molten aluminum, the obtained molten aluminum flows out through a front box and a casting nozzle, comes into contact with a moving titanium strip, and is cast and rolled under a casting mill to be composited, the surface roughness of the titanium strip is 1 to 8 μm, the preheating temperature of the titanium strip is 20 to 500°C, the casting and rolling speed is 0.5 to 2.0 m / min, and the cooling water flow rate of the rolling rolls is set to 3000 to 4000 L / h, and the liquid aluminum and solid titanium are composited by casting and rolling to form the titanium-aluminum composite strip material.
[0016] More preferably, in the specific manufacturing method of the titanium-aluminum composite strip material, an aluminum alloy is melted to obtain molten aluminum, the obtained molten aluminum flows out through a front box and a casting nozzle, comes into contact with a moving titanium strip, and is cast and rolled under a casting mill to be composited, and before the titanium strip is composited, the surface of the titanium strip is polished to remove the oxide film until the roughness is 4 to 6 μm, and laser etching is performed under argon gas to improve the mechanical strength and bonding strength of the titanium-aluminum composite strip material. The preheating temperature of the titanium strip is 400°C, the casting and rolling speed is 1.0 m / min, and the cooling water flow rate of the rolling rolls is set to 4000 L / h, and the liquid aluminum and solid titanium are composited by casting and rolling to form the titanium-aluminum composite strip material crude product.
[0017] In this invention, during a hot finishing rolling process involving large deformations, the combination of high pressure and high temperature regenerates composite layer material at the titanium-aluminum bonding interface, thereby improving the bonding effect. This technical method improves the refinement effect of alloy crystal grains, and simultaneously incorporates a large amount of high-density dislocations, dislocation cells, and substructures within the microstructure. Through a combination of fine crystal strengthening and dislocation strengthening, the strength of the titanium-aluminum composite strip material is effectively improved, and a good yield rate of processed titanium-aluminum composite material can be ensured. Furthermore, good bonding performance between the titanium strip and the aluminum strip is ensured.
[0018] More preferably, the temperature of the molten aluminum in the cast-rolled composite is 665-700°C, and the casting rate is 0.5-2.0 m / min.
[0019] More preferably, the temperature of the molten aluminum in the cast-rolled composite is 680°C, and the casting rate is 1.0 m / min.
[0020] By adopting the above technical proposal, the strength and bonding performance of the titanium-aluminum composite strip material can be further improved.
[0021] Preferably, in a specific manufacturing method for a first-grade titanium-aluminum composite strip material, the obtained first-grade titanium-aluminum composite strip material is subjected to a hot finishing rolling process with a large deformation at 400 to 600°C, and then removed and returned to room temperature.
[0022] By adopting the above technical proposal, hot finishing rolling with large deformations can regenerate composite layer material, improve bonding effects, and control the thickness of the strip material.
[0023] Preferably, in the specific manufacturing method for a second-grade titanium-aluminum composite strip material, the roughness of the working rolls during the cold finishing rolling process of the obtained first-grade titanium-aluminum composite strip material is ≤0.5 μm, the deformation amount in a single pass is ≤5%, and the total deformation amount is 2-10%.
[0024] The purpose of the cold finish rolling described above is to improve the flatness of the finished titanium-aluminum strip material, and to uniformly redistribute the internal stress of the material through rolling with a small deformation amount, so that the mechanical properties of the composite strip material can be further improved.
[0025] The narrow-width titanium-aluminum solid-liquid composite material is used in the fields of new energy, power busbars, copper-aluminum busbars, heat sinks, consumer electronic products, semiconductors, communications, satellites, computers, wind power and hydrogen energy, lithium batteries, photovoltaic power generation, military industry, robots, travel equipment, medical devices, aerospace, and 3C.
[0026] Preferably, in the field of 3C consumer electronic products, specifically, the narrow-width titanium-aluminum solid-liquid composite material produced by using the narrow-width titanium-aluminum solid-liquid composite material as the body material of high-end smartphones or the material for structural members of high-end smartphones has the advantages of light weight, high strength, corrosion resistance and good texture, which contributes to improving the appearance design of smartphones and can greatly reduce the weight of the body.
Effects of the Invention
[0027] As described above, the present application has the following advantages.
[0028] 1. The titanium-aluminum solid-liquid composite material produced by the present invention has both good mechanical strength and bonding strength. When used in the field of 3C consumer electronic products, it contributes to improving the appearance texture of smartphones. Compared with pure titanium materials, the titanium-aluminum composite material can greatly reduce the weight of the body and meet the lightweight design demand of smartphones.
[0029] 2. The production method of the present invention is simpler, has low operational difficulty, and is convenient for realizing industrialized production.
Brief Description of the Drawings
[0030] [Figure 1] This is a scanning electron microscope (SEM) image of the titanium-aluminum solid-liquid composite material interface in Example 1. [Modes for carrying out the invention]
[0031] To further understand the ingenuity and technological advancements of the present invention, preferred means of carrying out the invention will be described in detail below, along with examples and comparative examples. These specific examples are not limitations of the present invention, but merely illustrate the technical aspects of the invention. Those skilled in the art may, after reading this specification, make non-creative modifications to these examples as needed, but should be noted that such modifications will be protected under patent law as long as they fall within the scope of the claims of the present invention.
[0032] Examples The narrow titanium-aluminum solid-liquid composite material includes an aluminum strip formed by casting and rolling a titanium strip and liquid aluminum, wherein the titanium strip is made of pure titanium or a titanium alloy, and the aluminum strip is made of one of the following: 1-series pure aluminum, 3-series aluminum alloy, 5-series aluminum alloy, and 6-series aluminum alloy. The narrow titanium-aluminum solid-liquid composite material in this invention can be manufactured by processing a process that includes, but is not limited to, molded materials, strip materials, and sheet materials, resulting in titanium-aluminum solid-liquid composite materials with irregular shapes.
[0033] The peel strength between the titanium strip and the aluminum strip is ≥65 N / mm, the tensile strength of the narrow titanium-aluminum solid-liquid composite material is ≥300 MPa, the yield strength is ≥200 MPa, the composite surface shear strength is ≥180 MPa, and the elongation is ≥20%.
[0034] In the method for manufacturing narrow-width titanium-aluminum solid-liquid composite materials, first, titanium strips and liquid aluminum are cast and rolled together to obtain a rough titanium-aluminum composite strip material. Then, the rough titanium-aluminum composite strip material is subjected to a hot finishing rolling process at 400-600°C with a large amount of deformation to obtain a first-grade titanium-aluminum composite strip material. After cooling, a cold finishing rolling process with a small amount of deformation is performed to obtain a second-grade titanium-aluminum composite strip material. Finally, the second-grade titanium-aluminum composite strip material is straightened and polished to obtain the finished narrow-width titanium-aluminum solid-liquid composite material.
[0035] Preferably, the ratio of the thickness of the titanium strip to the thickness of the aluminum strip in the titanium-aluminum composite strip material is 1:(2-3), and more preferably, the ratio of the thickness of the titanium strip to the thickness of the aluminum strip in the titanium-aluminum composite strip material is 1:2. The amount of deformation of the titanium-aluminum composite strip material during the hot finishing rolling process with large deformation is 50-70%.
[0036] In a cold finishing rolling process with small deformation, the number of cold finishing rolls is one or two. The total deformation of the Grade 1 titanium-aluminum composite strip material during the cold finishing rolling process is 2-10%, and the deformation of a single pass is ≤5%.
[0037] Specifically, the method for producing a narrow titanium-aluminum solid-liquid composite material includes the following steps:
[0038] S1. In the specific manufacturing method of titanium-aluminum composite strip material crude product, an aluminum alloy is melted to obtain molten aluminum, the obtained molten aluminum flows out through the front box and casting nozzle, comes into contact with the moving titanium strip, and is cast and rolled under a casting mill to be composited, the titanium strip is polished to remove the oxide film until the surface roughness is 1 to 8 μm before composite, the titanium strip is preheated to a temperature of 20°C to 500°C, the casting and rolling speed is 0.5 to 2.0 m / min, and the cooling water flow rate of the rolling rolls is set to 3000 to 4000 L / h, and the liquid aluminum and solid titanium are composited by casting and rolling to form titanium-aluminum composite strip material crude product. Preferably, the titanium strip has a surface roughness of 4-6 μm, the titanium strip is preheated to 400°C, the casting and rolling speed is 1 m / min, the cooling water flow rate of the rolling rolls is set to 4000 L / h, and the liquid aluminum and solid titanium are combined by casting and rolling to form a titanium-aluminum composite strip material. Preferably, the temperature of the molten aluminum in the cast-rolled composite is 665 to 700°C, and the casting speed is 0.5 to 2.0 m / min. More preferably, the temperature of the molten aluminum in the cast-rolled composite is 680°C, and the casting speed is 1.0 m / min.
[0039] S2. In the specific manufacturing method for Grade 1 Titanium-Aluminum Composite Strip Material Crude Product, the obtained Titanium-Aluminum Composite Strip Material Crude Product is subjected to a hot finish rolling treatment with a large deformation amount, the temperature being 400-600°C, the deformation amount being 50-70%, and the rolling speed being 0.5-5.0 m / min, preferably 2-3.0 m / min. By returning it to room temperature, a crude product of first-grade titanium-aluminum composite strip material can be obtained.
[0040] S3. In the specific manufacturing method for Grade 2 titanium-aluminum composite strip material, Grade 1 titanium-aluminum composite strip material is subjected to cold finishing rolling with small deformation amounts 1 to 2 times, with a working roll roughness of ≤0.5 μm, a single-pass deformation amount of ≤5%, and a total deformation amount of 2 to 10%, thereby obtaining Grade 2 titanium-aluminum composite strip material.
[0041] The crude secondary titanium-aluminum composite strip material obtained in S4 and S3 can be straightened and polished to obtain the finished narrow-width titanium-aluminum solid-liquid composite material.
[0042] The narrow titanium-aluminum solid-liquid composite material produced can be used in the new energy sector, power busbar sector, copper-aluminum busbar sector, heat sink sector, consumer electronics sector, semiconductor sector, communications sector, satellite sector, computer sector, wind and hydrogen energy sector, lithium battery sector, solar power generation sector, defense industry sector, robotics sector, travel equipment sector, medical equipment sector, aerospace sector, and 3C sector.
[0043] Preferably, narrow titanium-aluminum solid-liquid composite materials are used in the field of 3C consumer electronic products. Specifically, narrow titanium-aluminum solid-liquid composite materials manufactured as body materials or structural component materials for high-end smartphones have advantages such as being lightweight, having high strength, corrosion resistance, and good texture. This contributes to improving the aesthetics and texture of the smartphone's exterior design, while also significantly reducing the body weight and meeting the demand for lightweight smartphone designs.
[0044] The raw materials are sourced as follows: Titanium strips, Titanium Strip TA2, Baoji Nucleon Sea Titanium Nickel Co., Ltd.; 6061 series aluminum alloy, Dongguan Yida Metal Materials Co., Ltd.
[0045] The specific preferred means of implementation are as follows:
[0046] Example 1: A method for producing a narrow titanium-aluminum solid-liquid composite material was carried out as follows. S1. First, the titanium strip is polished to remove impurities such as oxides from the surface, and then polished sequentially with 500# sandpaper, 1000# sandpaper, 2000# sandpaper, 5000# sandpaper, and 10000# sandpaper until the roughness reaches 1.7 μm. In the specific manufacturing method for the titanium-aluminum composite strip material, a 6061 aluminum alloy was heated to 680°C and melted to obtain molten aluminum. The obtained molten aluminum flowed out through a front box and casting nozzle, came into contact with a polished titanium strip in transit, and was cast and rolled under a casting mill to composite the materials. The surface roughness of the titanium strip was 1.7 μm, the casting speed was 1.0 mm / min, the preheating temperature of the titanium strip was 500°C, the casting and rolling speed was 1.0 m / min, and the cooling water flow rate of the rolling rolls was set to 3000 L / h. The liquid aluminum and solid titanium were composited by casting and rolling to form the titanium-aluminum composite strip material. In the titanium-aluminum composite strip material, the thickness of the titanium strip was 4 mm, the thickness of the aluminum strip was 8 mm, and the total thickness of the titanium-aluminum composite strip material was 12 mm.
[0047] S2. In the specific manufacturing method for the Grade 1 Titanium-Aluminum Composite Strip Material, the obtained Titanium-Aluminum Composite Strip Material was subjected to a hot finishing rolling process with a large deformation amount at a temperature of 500°C, a deformation amount of 50%, and a rolling speed of 0.5 m / min, resulting in a thickness of 6 mm for the Grade 1 Titanium-Aluminum Composite Strip Material.
[0048] In S3. The specific manufacturing method for the Grade II titanium-aluminum composite strip material rough product, the obtained Grade I titanium-aluminum composite strip material rough product was subjected to one cold finishing rolling treatment with a small deformation amount, using a working roll roughness of 0.5 μm and a deformation amount of 5%, to obtain a Grade II titanium-aluminum composite strip material rough product with a thickness of 5.7 mm.
[0049] The crude second-grade titanium-aluminum composite strip material obtained in S4 and S3 was straightened and polished to obtain the finished narrow-width titanium-aluminum solid-liquid composite material.
[0050] Referring to Figure 1, scanning electron microscope (SEM) images of the titanium-aluminum solid-liquid composite interface were imaged using a backscatter electron detector (BSD), clearly showing the microstructural features of the interface region in backscatter electron mode. The images showed that the morphology of the titanium / aluminum interface bonding region was continuous, there were no obvious macrodefects, the interface transition was gradual, and a good metallurgical bond existed between the two phases. The difference in backscatter electron contrast was significant, reflecting the component region characteristics due to the difference in atomic numbers of the two phases of titanium and aluminum. A diffusion reaction layer was observed at the interface, the microstructure exhibited a gradient transition, and no obvious pores, cracks, or inclusions were observed near the interface, indicating good microstructural compatibility between the bonding region and the substrate.
[0051] The difference between Example 2 and Example 1 is that in S1, the titanium strip was first polished to remove impurities such as oxides from the surface, and then polished sequentially with 500# sandpaper, 1000# sandpaper, 2000# sandpaper, and 5000# sandpaper until the roughness reached 3.5 μm, while all other steps were the same in both examples.
[0052] The difference between Example 3 and Example 1 is that in S1, the titanium strip was first polished to remove impurities such as oxides from the surface, and then polished sequentially with 500# sandpaper, 1000# sandpaper, 2000# sandpaper, and 3000# sandpaper until the roughness reached 4.7 μm, while all other steps were the same in both examples.
[0053] The difference between Example 4 and Example 1 is that in S1, the titanium strip was first polished to remove impurities such as oxides from the surface, and then polished sequentially with 500# sandpaper, 1000# sandpaper, 2000# sandpaper, and 2500# sandpaper until the roughness reached 5.9 μm, while all other steps were the same in both examples.
[0054] The difference between Example 5 and Example 1 is that in S1, the titanium strip was first polished to remove impurities such as oxides from the surface, and then polished sequentially with 500# sandpaper, 1000# sandpaper, and 2000# sandpaper until the roughness reached 7.8 μm; all other steps were the same in both examples.
[0055] The difference between Example 6 and Example 1 is that, in S1, the titanium strip was first polished to remove impurities such as oxides from the surface, and polished sequentially with 500# sandpaper, 1000# sandpaper, 2000# sandpaper, and 2500# sandpaper until the roughness reached 5.9 μm, and then the polished titanium strip was laser etched in an argon gas atmosphere with a laser power of 25 W, a voltage of 220 V, a repeatability of 0.25 mm, and an etching speed of 2000 mm / s, and the laser-etched titanium strip was cast and rolled and composited with liquid aluminum to form a titanium-aluminum composite strip material. All other steps were the same in both cases.
[0056] The difference between Comparative Example 1 and Example 1 is that in Example 1, the titanium strip was not polished, and the unpolished titanium strip was cast and rolled, then composited with liquid aluminum to form a crude titanium-aluminum composite strip material; all other steps were the same.
[0057] The difference between Comparative Example 2 and Example 1 is that, in S1, the titanium strip was first polished to remove impurities such as oxides from the surface, and then polished sequentially with 500# sandpaper, 1000# sandpaper, and 1340# sandpaper until the roughness reached 10.2 μm; all other steps were the same in both cases.
[0058] The difference between Comparative Example 3 and Example 1 is that in S1, an unpolished titanium strip was laser-etched in an air atmosphere with a laser power of 25W, a voltage of 220V, a repeatability of 0.25mm, and an etching speed of 2000mm / s, and the titanium strip obtained by laser etching was cast and rolled and composited with liquid aluminum to form a crude titanium-aluminum composite strip material. All other steps were the same.
[0059] Test Method 1: In accordance with the requirements for metal tensile and delamination samples in GB / T 228-2002, tensile and delamination samples were cut from titanium-aluminum composite sheet material. Delamination samples were processed using wire cutting in accordance with GB / T 2791-1995. Tensile and delamination tests were performed on a universal testing machine (model CMT5105). Due to the thickness of the aluminum sheet, in the delamination test, the aluminum sheet was fixed to the lower end and a titanium strip was sandwiched between the upper end to tensile delamination. The delamination strength of the titanium-aluminum composite sheet was obtained by data analysis.
[0060] Table 1: Test parameters for titanium-aluminum composite strips in Examples 1-6 and Comparative Examples 1-3 [Table 1]
[0061] As can be seen from the combination of Examples 1-6 and Comparative Examples 1-3 and Table 1, the surface roughness of the titanium strips after polishing was controlled to 1-8 micrometers, and the manufactured titanium-aluminum composite strip material exhibited excellent mechanical strength and bonding strength.
[0062] As can be seen from the combination of Example 6, Example 4, and Comparative Example 3 with Table 1, after polishing the titanium strip until the surface roughness was 4 to 6 micrometers, laser etching was performed under argon gas. The mechanical strength of the titanium-aluminum composite strip material produced in Example 6 was improved to some extent compared to the titanium-aluminum composite strip material in Example 4 and Comparative Example 3. The bonding strength of the titanium-aluminum composite strip material produced in Example 6 was clearly improved compared to the bonding strength of the titanium-aluminum composite strip material in Example 4 and Comparative Example 3. Polishing the titanium strip until the surface roughness was 4 to 6 micrometers, followed by laser etching under argon gas, improved the mechanical strength and bonding strength of the titanium-aluminum composite strip material.
[0063] The difference between Example 7 and Example 6 is that the preheating temperature of the titanium strip after polishing was 20°C.
[0064] The difference between Example 8 and Example 6 is that the preheating temperature of the titanium strip after polishing was 100°C.
[0065] The difference between Example 9 and Example 6 is that the preheating temperature of the titanium strip after polishing was 200°C.
[0066] The difference between Example 10 and Example 6 is that the preheating temperature of the titanium strip after polishing was 400°C.
[0067] The difference between Comparative Example 4 and Example 6 is that the preheating temperature of the titanium strip after polishing was 10°C.
[0068] The difference between Comparative Example 5 and Example 6 is that the preheating temperature of the titanium strip after polishing was 500°C.
[0069] Table 2: Test parameters for titanium-aluminum composite strips in Examples 6-10 and Comparative Examples 4-5 [Table 2]
[0070] As can be seen from the combination of Examples 6-10 and Comparative Examples 4-5 and Table 2, by controlling the preheating temperature of the polished titanium strip to 20-400°C, it is possible to ensure that the manufactured titanium-aluminum composite strip material has excellent mechanical strength and bonding strength, and preferably the preheating temperature of the polished titanium strip is controlled to 400°C. If the preheating temperature of the polished titanium strip is too high, an oxide layer is likely to form on the surface of the titanium strip, which is detrimental to improving the overall interlayer bonding strength.
[0071] The difference between Example 11 and Example 8 is that the casting and rolling speed was 0.5 m / min.
[0072] The difference between Example 12 and Example 8 is that the casting and rolling speed was 1.5 m / min.
[0073] The difference between Example 13 and Example 8 is that the casting and rolling speed was 2.0 m / min.
[0074] The difference between Comparative Example 6 and Example 8 is that the casting and rolling speed was 0.25 m / min.
[0075] The difference between Comparative Example 7 and Example 8 is that the casting and rolling speed was 2.5 m / min.
[0076] Table 3: Test parameters for titanium-aluminum composite strips in Examples 8, 11-13, and Comparative Examples 6-7. [Table 3]
[0077] As can be seen from the combination of Examples 8, 11-13 and Comparative Examples 6-7 with Table 3, controlling the casting and rolling speed to 0.5-2.0 m / min in S1 resulted in excellent mechanical strength and bonding strength of the manufactured titanium-aluminum composite strip material. Considering production efficiency and product performance comprehensively, controlling the casting and rolling speed to 1.0-1.5 m / min in S1 is preferable.
[0078] The difference between Example 14 and Example 1 is that the thickness of the titanium-aluminum composite strip material was 12 mm, the thickness of the titanium strip was 3 mm, and the thickness of the aluminum strip was 9 mm.
[0079] The difference between Example 15 and Example 1 is that the thickness of the titanium-aluminum composite strip material was 12 mm, the thickness of the titanium strip was 3.5 mm, and the thickness of the aluminum strip was 8.5 mm.
[0080] The difference between Comparative Example 8 and Example 1 is that the thickness of the titanium-aluminum composite strip material was 12 mm, the thickness of the titanium strip was 5 mm, and the thickness of the aluminum strip was 7 mm.
[0081] The difference between Comparative Example 9 and Example 1 is that the thickness of the titanium-aluminum composite strip material was 12 mm, the thickness of the titanium strip was 6 mm, and the thickness of the aluminum strip was 6 mm.
[0082] Table 4: Test parameters for titanium-aluminum composite strips in Example 1, Examples 14-15 and Comparative Examples 8-9 [Table 4]
[0083] As can be seen from the combination of Examples 1, 14-15 and Comparative Examples 8-9 with Table 4, the ratio of the thickness of the titanium strip to the thickness of the aluminum strip in the crude titanium-aluminum composite strip material was 1:(2-3), and the resulting titanium-aluminum composite strip material exhibited excellent mechanical strength and bonding strength. Considering energy consumption costs and product performance comprehensively, the ratio of the thickness of the titanium strip to the thickness of the aluminum strip is preferably 1:2.
[0084] The difference between Example 16 and Example 15 is that the cooling water flow rate for the rolling rolls was 3300 L / h.
[0085] The difference between Example 17 and Example 15 is that the cooling water flow rate for the rolling rolls was 3700 L / h.
[0086] The difference between Example 18 and Example 15 is that the cooling water flow rate for the rolling rolls was 4000 L / h.
[0087] The difference between Comparative Example 10 and Example 15 is that the cooling water flow rate for the rolling rolls was 2800 L / h.
[0088] The difference between Comparative Example 11 and Example 15 is that the cooling water flow rate for the rolling rolls was 4200 L / h.
[0089] Table 5: Test parameters for titanium-aluminum composite strips in Examples 15-18 and Comparative Examples 10-11 [Table 5]
[0090] As can be seen from the combination of Examples 15-18 and Comparative Examples 10-11 with Table 5, in S1, the cooling water flow rate of the rolling rolls was 3000-4000 L / h, and the resulting titanium-aluminum composite strip material exhibited excellent mechanical strength and bonding strength. In S1, the cooling water flow rate of the rolling rolls had a clear effect on the mechanical strength and bonding strength of the titanium-aluminum composite strip material, and preferably in S2, the cooling water flow rate of the rolling rolls was 4000 L / h, resulting in excellent overall performance of the titanium-aluminum composite strip material.
[0091] The difference between Example 19 and Example 18 is that, in S2. Specific manufacturing method for Grade 1 Titanium-Aluminum Composite Strip Material, the obtained Titanium-Aluminum Composite Strip Material was subjected to a large deformation hot finishing rolling process with a deformation amount of 50% and a rolling speed of 1.0 m / min, resulting in a thickness of 6 mm for the Grade 1 Titanium-Aluminum Composite Strip Material. The difference between Example 20 and Example 18 is that, in S2. Specific manufacturing method of Grade 1 Titanium-Aluminum Composite Strip Material, the obtained Titanium-Aluminum Composite Strip Material was subjected to a hot finishing rolling process with a large deformation amount of 50% and a rolling speed of 2.0 m / min, resulting in a thickness of 6 mm for the Grade 1 Titanium-Aluminum Composite Strip Material.
[0092] The difference between Example 21 and Example 18 is that, in S2. Specific manufacturing method of Grade 1 Titanium-Aluminum Composite Strip Material, the obtained Titanium-Aluminum Composite Strip Material was subjected to a large deformation hot finishing rolling process at a deformation amount of 50% and a rolling speed of 2.5 m / min, resulting in a thickness of 6 mm for the Grade 1 Titanium-Aluminum Composite Strip Material.
[0093] The difference between Example 22 and Example 18 is that, in S2. Specific manufacturing method of Grade 1 Titanium-Aluminum Composite Strip Material, the obtained Titanium-Aluminum Composite Strip Material Material was subjected to a hot finishing rolling process with a large deformation amount of 50% and a rolling speed of 3.0 m / min, resulting in a thickness of 6 mm for the Grade 1 Titanium-Aluminum Composite Strip Material Material Material.
[0094] The difference between Example 23 and Example 18 is that, in S2. Specific manufacturing method of Grade 1 Titanium-Aluminum Composite Strip Material, the obtained Titanium-Aluminum Composite Strip Material was subjected to a large deformation hot finishing rolling process with a deformation amount of 50% and a rolling speed of 4.0 m / min, resulting in a thickness of 6 mm for the Grade 1 Titanium-Aluminum Composite Strip Material.
[0095] The difference between Example 24 and Example 18 is that in S2. Specific manufacturing method of Grade 1 Titanium-Aluminum Composite Strip Material, the obtained Titanium-Aluminum Composite Strip Material was subjected to a large deformation hot finishing rolling process at a deformation amount of 50% and a rolling speed of 5.0 m / min, resulting in a thickness of 6 mm for the Grade 1 Titanium-Aluminum Composite Strip Material.
[0096] The difference between Comparative Example 12 and Example 18 is that, in S2. Specific manufacturing method of Grade 1 Titanium-Aluminum Composite Strip Material, the obtained Titanium-Aluminum Composite Strip Material Material was subjected to a hot finishing rolling process with a large deformation amount of 50% and a rolling speed of 0.4 m / min, resulting in a thickness of 6 mm for the Grade 1 Titanium-Aluminum Composite Strip Material Material Material.
[0097] The distinction between Comparative Example 13 and Example 18 is that, in S2. The specific manufacturing method for the Grade 1 Titanium-Aluminum Composite Strip Material, the obtained Titanium-Aluminum Composite Strip Material was subjected to a hot finishing rolling process with a large deformation amount of 50% and a rolling speed of 6 m / min, resulting in a thickness of 6 mm for the Grade 1 Titanium-Aluminum Composite Strip Material.
[0098] Table 6: Test parameters for titanium-aluminum composite strips in Examples 18-24 and Comparative Examples 12-13 [Table 6]
[0099] As can be seen from the combination of Examples 18-24 and Comparative Examples 12-13 with Table 6, in S2, controlling the casting and rolling speed to 0.5-5.0 m / min results in excellent mechanical strength and bonding strength of the titanium-aluminum composite strip material. Preferably, in S2, the casting and rolling speed is 2-3 m / min, resulting in excellent overall performance of the obtained titanium-aluminum composite strip material and high production efficiency.
[0100] The difference between Example 25 and Example 21 is that, in S3. Specific manufacturing method for Grade 2 titanium-aluminum composite strip material, the obtained Grade 1 titanium-aluminum composite strip material was subjected to one cold finishing rolling treatment with a working roll roughness of 0.5 μm and a total deformation of 4%, thereby obtaining a Grade 2 titanium-aluminum composite strip material with a thickness of 5.76 mm.
[0101] The distinction between Example 26 and Example 25 is, S3. The specific manufacturing method for the Grade 2 titanium-aluminum composite strip material rough product involves performing cold finishing rolling twice on the obtained Grade 1 titanium-aluminum composite strip material rough product with a working roll roughness of 0.5 μm and a total deformation of 4%, thereby obtaining a Grade 2 titanium-aluminum composite strip material rough product with a thickness of 5.76 mm.
[0102] The difference between Comparative Example 14 and Example 26 is that, in S3. Specific manufacturing method of Grade 2 Titanium-Aluminum Composite Strip Material, the obtained Grade 1 Titanium-Aluminum Composite Strip Material rough product was subjected to one cold finishing rolling treatment with a working roll roughness of 0.5 μm and a total deformation of 6%, thereby obtaining a Grade 2 Titanium-Aluminum Composite Strip Material rough product with a thickness of 5.64 mm.
[0103] The difference between Comparative Example 15 and Example 26 is that, in S3. Specific manufacturing method of Grade 2 Titanium-Aluminum Composite Strip Material, the obtained Grade 1 Titanium-Aluminum Composite Strip Material Material was subjected to two cold finishing rolling processes with a working roll roughness of 0.5 μm, a single-pass deformation of 6%, and a total deformation of 12%, thereby obtaining a Grade 2 Titanium-Aluminum Composite Strip Material Material Material with a thickness of 5.28 mm.
[0104] The difference between Example 27 and Example 26 is that, in S3. Specific manufacturing method for Grade 2 titanium-aluminum composite strip material, the obtained Grade 1 titanium-aluminum composite strip material rough product was subjected to one cold finishing rolling treatment with a working roll roughness of 0.5 μm and a total deformation of 5%, thereby obtaining a Grade 2 titanium-aluminum composite strip material rough product with a thickness of 5.7 mm.
[0105] The difference between Example 28 and Example 26 is that, in S3. Specific manufacturing method for Grade 2 titanium-aluminum composite strip material, the obtained Grade 1 titanium-aluminum composite strip material was subjected to two cold finishing rolling processes with a working roll roughness of 0.5 μm and a total deformation of 5%, thereby obtaining a Grade 2 titanium-aluminum composite strip material with a thickness of 1.0 mm.
[0106] The distinction between Example 29 and Example 26 is, S3. The specific manufacturing method for the Grade 2 titanium-aluminum composite strip material rough product involves performing cold finishing rolling three times on the obtained Grade 1 titanium-aluminum composite strip material rough product with a working roll roughness of 0.5 μm and a total deformation of 4%, thereby obtaining a Grade 2 titanium-aluminum composite strip material rough product with a thickness of 5.76 mm.
[0107] Table 7: Test parameters for titanium-aluminum composite strips in Examples 21, 25-29 and Comparative Examples 14-15 [Table 7]
[0108] As can be seen from the combination of Examples 21, 25-29 and Comparative Examples 14-15 with Table 7, the titanium-aluminum composite strips produced by subjecting the obtained first-grade titanium-aluminum composite strip material to one to two small-deformation cold finishing rolls with a working roll roughness of ≤0.5 μm, a single-pass deformation of ≤5%, and a total deformation of 2-12% exhibited excellent mechanical strength and bonding strength. Considering production efficiency and product performance comprehensively, it is preferable to control the number of cold finishing rolls to one or two. As seen from Example 29, increasing the number of cold finishing rolls has little impact on performance, but it increases costs, so it is not necessary to increase it too much. Comparative Examples 14 and 15 show that the deformation amount in single-pass cold finishing rolling should not be too large and should be controlled to 5% or less. Analysis indicates that cold finishing rolling reduces the composite effect of the composite material and is mainly used to adjust the thickness accuracy of the composite material. If the deformation amount in cold finishing rolling is too large, it has a significant impact on the performance of the composite material, and the decrease in peel strength is particularly large. A comprehensive analysis shows that the number of cold finishing rolls should be controlled to two or less, and the deformation amount in single-pass cold finishing rolling should be ≤5%.
[0109] As described above, the titanium-aluminum solid-liquid composite material manufactured according to the present invention possesses excellent mechanical strength and bonding strength. Through optimization of manufacturing process parameters, the manufactured titanium-aluminum solid-liquid composite strip material exhibits a tensile strength of ≥300 MPa, a yield strength of ≥200 MPa, a composite surface shear strength of ≥180 MPa, an elongation of ≥20%, and a peel strength of ≥60 N / mm². 2 Therefore, when used in the field of 3C consumer electronics products, it contributes to improving the appearance and texture of smartphones, while also significantly reducing the weight of the body, thus meeting the demand for lightweight smartphone designs.
Claims
1. A narrow titanium-aluminum solid-liquid composite material, It includes a titanium strip and an aluminum strip formed by casting and rolling liquid aluminum, The material of the titanium strip is pure titanium or a titanium alloy. The aluminum strip is one of the following: 1-series pure aluminum, 3-series aluminum alloy, 5-series aluminum alloy, and 6-series aluminum alloy. Peel strength between the titanium strip and the aluminum strip ≥ 60 N / mm 2 The narrow titanium-aluminum solid-liquid composite material is characterized in that it has a tensile strength of ≥300 MPa, a yield strength of ≥200 MPa, a composite surface shear strength of ≥180 MPa, and an elongation of ≥20%.
2. In the method for producing the aforementioned narrow titanium-aluminum solid-liquid composite material, The narrow-width titanium-aluminum solid-liquid composite material according to claim 1, characterized in that first, a titanium strip and liquid aluminum are cast and rolled together to obtain a titanium-aluminum composite strip material rough product, then a large deformation hot finishing rolling treatment is performed on the titanium-aluminum composite strip material rough product at 400 to 600°C to obtain a first-grade titanium-aluminum composite strip material rough product, after cooling treatment a small deformation cold finishing rolling treatment is performed to obtain a second-grade titanium-aluminum composite strip material rough product, and finally the second-grade titanium-aluminum composite strip material rough product is straightened and polished to obtain a finished narrow-width titanium-aluminum solid-liquid composite material.
3. The narrow titanium-aluminum solid-liquid composite material according to claim 2, characterized in that the ratio of the thickness of the titanium strip to the thickness of the aluminum strip in the titanium-aluminum composite strip material crude product is 1:(2-3).
4. The narrow titanium-aluminum solid-liquid composite material according to claim 2, characterized in that the amount of deformation of the titanium-aluminum composite strip material crude product during the hot finishing rolling process with large deformation amounts is 50 to 70%.
5. The narrow titanium-aluminum solid-liquid composite material according to claim 2, characterized in that, in a cold finishing rolling process with a small amount of deformation, the number of cold finishing rolling cycles is one or two, and the amount of deformation of the crude first-grade titanium-aluminum composite strip material in a single cold finishing rolling process is ≤5%.
6. In the specific manufacturing method of the aforementioned titanium-aluminum composite strip material, The narrow titanium-aluminum solid-liquid composite material according to claim 2, characterized in that an aluminum alloy is melted to obtain molten aluminum, the obtained molten aluminum flows out through a front box and a casting nozzle, comes into contact with a moving titanium strip, is cast and rolled under a casting and rolling mill to be composited, the surface roughness of the titanium strip is 1 to 8 μm, the preheating temperature of the titanium strip is 20°C to 500°C, the casting and rolling speed is 0.5 to 2.0 m / min, the cooling water flow rate of the rolling rolls is set to 3000 to 4000 L / h, and the liquid aluminum and solid titanium are composited by casting and rolling to form a crude titanium-aluminum composite strip material.
7. The narrow titanium-aluminum solid-liquid composite material according to claim 6, characterized in that the temperature of the molten aluminum during casting and rolling is 665 to 700°C, and the casting rate is 0.5 to 2.0 m / min.
8. In the specific manufacturing method of the aforementioned titanium-aluminum composite strip material, The aluminum alloy is melted to obtain molten aluminum, which flows out through the front box and casting nozzle, comes into contact with a moving titanium strip, and is cast and rolled under a casting mill to be compounded. The narrow titanium-aluminum solid-liquid composite material according to claim 2, characterized in that, before compounding the titanium strip, the surface roughness is polished to remove the oxide film until it reaches 4 to 8 micrometers, then laser-etched under argon gas, the preheating temperature of the titanium strip is 400°C, the casting and rolling speed is 1 m / min, the cooling water flow rate of the rolling rolls is set to 4000 L / h, and liquid aluminum and solid titanium are compounded by casting and rolling to form a rough titanium-aluminum composite strip material.
9. The narrow titanium-aluminum solid-liquid composite material according to claim 8, characterized in that the temperature of the molten aluminum during casting and rolling is 680°C and the casting rate is 1.0 m / min.
10. The narrow titanium-aluminum solid-liquid composite material according to claim 9, characterized in that the ratio of the thickness of the titanium strip to the thickness of the aluminum strip in the crude titanium-aluminum composite strip material is 1:2.